Pengembangan Aplikasi Mobile Berbasis Android untuk Mendukung Strategi Pemasaran dan Penjualan pada UMKM Saung Batik Baswet - Manurung, Ria; Lianawati, Yosita; Sipahutar, Tetty Tiurma Uli (LPPM Poltek ST Paul, 2025)
One MSME sector with high potential to grow is the batik handicraft industry. Saung Batik Baswet is one of the MSMEs engaged in producing and selling local batik in Banyumas Regency by trying to preserve cultural heritage while creating economic value. Marketing carried out by Saung Batik Baswet is still carried out conventionally, and it is still limited to social media, WhatsApp, Instagram, relations between relations, friends and relatives, and word of mouth. The research aims to develop Android-based mobile applications that can support marketing activities and product sales at Saung Batik Baswet MSMEs and evaluate the effectiveness of applications in increasing marketing efficiency and customer convenience in making transactions. The research uses a prototyping method that allows application development to be carried out iteratively and based on user feedback. The research results with the Paired Samples Test concluded that H0 was rejected and H1 was accepted because the Sig. The value obtained was 0.00, which means the Sig. Value is less than 0.05. So, there is a significant time difference when ordering a menu before and after using the Saung Batik Baswet Android mobile application. These results indicate that the developed application has successfully increased efficiency in the ordering process, which undoubtedly contributes to improving the customer experience in making transactions.